Developing indonesia’s natural gas transportation business regulation - Lede Mude Ragawino, Ocktavianus; Anggoro, Yudo (The Indonesian Journal of Business Administration, 2018)
Abstract - After decades natural gas been country revenue, Indonesia had changed the mindset that natural gas should be the motor for economic development. Regards to the natural gas transportation regulation, the government is planned to revise the regulation of Ministry Energy and Mineral Resources No 19/2009 to increase the natural gas transportation infrastructures. The natural gas industry is a network industry. Theoretically, a single company will be more economically efficient than two or more companies. Based on the experiences, the natural gas systems were initially developed by vertically integrated model while the competition was introduced when the market has enlarged since competition will attract new capital and enable new business opportunities. Potential evolutions of the current regulatory framework are bundled centralized- vertically integrated, unbundled centralized – centralized entity responsible for whole operation, and unbundled decentralized – private initiative. The distribution infrastructure development could rely in franchise auctions to offer concessions to distribution utilities. Considering the natural gas system Indonesia is still in young age and it has not mature yet, the regulation should be firstly in bundled centralized system which has advantageous in early stages by establishing Master Plan with franchise method for attracting company.Keywords: bundled centralized, franchise, integrated, Master Plan, mature